MATHEMATICS MODELLING AND EXPERIMENTAL STUDY THE EFFECT OF VORTEX WATER TURBINE BLADE DESIGN OF TURBINE EFFICIENCY - Fitriana, Laila; Saputro , Herman; Purwanto, Aris; Huda, Damar Sunanil; Muslim, Riyadi (Jurnal Rekayasa Mesin, 2025)
The current demand for electrical energy is crucial to support facilities and infrastructure across various sectors, including household, public, and industrial areas. In Indonesia, the reliance on fossil fuels for electricity generation remains high, contributing to significant emissions. Renewable energy sources, such as water energy, present a viable solution to mitigate these emissions and enhance environmental sustainability due to their eco-friendly and sustainable characteristics. Micro hydro energy can be generated by micro-scale power plants using hydropower by converting fluid rotation into electrical energy called Gravitational Water Vortex Power Plant. In water vortex power plant, the blades have a significant influence on the produced power of turbine. For this reason, it is necessary to have a suitable blades design to produce optimal power and efficiency. This study investigates the impact of different vortex turbine blade shapes straight blade, L blade, and curved blade. We used numerical and simulation to investigate the power and efficiency of vortex-type water turbines. Simulation results indicated significant effects of blade shape variations and the distance between blades and the outlet on turbine performance. The straight blade exhibited a tangential velocity of 2.95 m/s and torque of 1.49 Nm, producing 20.94 watts with an efficiency of 84.71%. The L blade demonstrated a tangential velocity of 2.84 m/s and torque of 1.54 Nm, yielding 20.82 watts with an efficiency of 84.3%. In contrast, the curved blade showed a tangential velocity of 2.83 m/s and torque of 1.21 Nm, generating 16.32 watts with an efficiency of 65.97%. Experimental testing revealed that the curved blade produced the highest power and efficiency at 11.64 watts and 23.56%, respectively. The optimal distance between the blade and the outlet was determined to be 2 cm, achieving the same power and efficiency values.